Finite strip analysis of bridges - Cheung, M.S (E & FN Spon, 1996)
In-depth, comprehensive and up-to-date information on the powerful finite strip method of analysis of bridges. It is in three parts. The first introduces the method and gives the necessary background. The second explains the evolution of the method and the third part provides detailed information on the application of the method to highway bridges.